Coping with Grief in Kathleen Glasgow's Novel How to Make Friends with the Dark (2019) - Sarifia Larasati Putri; Desvalini Anwar (Universitas Negeri Padang, 2023)
This thesis is a psychoanalysis reading of a novel which is written by Kathleen Glasgow entitled How to Make Friends with the Dark (2019). It explores the issue of coping with grief which is experienced by the main character while she is experiencing grief. It uses the qualitative method in analyzing the novel. The analysis of coping with grief is used the concept of Lazarus and Folkman (1984) of coping mechanism. It is also aimed to reveal how the main character copes with the grief. The result of this analysis shows that the main character copes with her grief through two ways, problem-focused coping and emotion-focused coping.